Darier disease - Godić, Aleksandar (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2003)
Darier disease (DD) is characterized by hyperkeratotic papules that coalesce into plaques and occur primarily in seborrheic or intertriginous areas. Associated findings include nail abnormalities, white papules of the oral mucosa, punctate keratoses, papules on the dorsum of the feet and hands, broken papillary lines on palms, as well as a variety of neurologic and psychic abnormalities. DD is an autosomal dofninant skin disorder caused by mutations of ATP2A2 gene. The gene encodes the sarco/endoplasmic reticulum Ca2+ ATPase isoform 2 (SERCA2 protein). SERCA pumps maintain low cytosolic Caz+ concentration which is important for the assembly of desmosomes. To date,122 mutations of ATP2A2 gene in Darier disease patients have been identified, scattered throughout the gene. No hotspot has been identified. Considerable phenotypic variations within and between families suggest that variety mechanisms in intracellular Ca2+ homeostasis exist.
Keywords: Ca(2+)-prenašalna ATPaza; Ca(2+)-Transporting Atpase; dermatologija; Diagnosis; Keratosis Follicularis; Keratoza folikularna; kožne bolezni; Physiopathology; Therapy